Hierarchical NiCo2O4 Hollow Sphere as a Peroxidase Mimetic for Colorimetric Detection of H2O2 and Glucose - Wei Huang; Tianye Lin; Yang Cao; Xiaoyong Lai; Juan Peng; Jinchun Tu (Sensors, 2017)
In this work, the hierarchical NiCo2O4 hollow sphere synthesized via a “coordinating etching and precipitating” process was demonstrated to exhibit intrinsic peroxidase-like activity. The peroxidase-like activity of NiCo2O4, NiO, and Co3O4 hollow spheres were comparatively studied by the catalytic oxidation reaction of 3,3,5,5-tetramethylbenzidine (TMB) in presence of H2O2, and a superior peroxidase-like activity of NiCo2O4 was confirmed by stronger absorbance at 652 nm. Furthermore, the proposed sensing platform showed commendable response to H2O2 with a linear range from 10 μM to 400 μM, and a detection limit of 0.21 μM. Cooperated with GOx, the developed novel colorimetric and visual glucose-sensing platform exhibited high selectivity, favorable reproducibility, satisfactory applicability, wide linear range (from 0.1 mM to 4.5 mM), and a low detection limit of 5.31 μM. In addition, the concentration-dependent color change would offer a better and handier way for detection of H2O2 and glucose by naked eye.